Gabapentin increases expression of δ subunit-containing GABA(A) receptors - Yu, Jieying (EBioMedicine, 2019)
BACKGROUND: Gabapentin is a structural analog of the inhibitory neurotransmitter γ-aminobutyric acid (GABA). Its anticonvulsant, analgesic and anxiolytic properties suggest that it increases GABAergic inhibition; however, the molecular basis for these effects is unknown as gabapentin does not directly modify GABA type A (GABA(A)) receptor function, nor does it modify synaptic inhibition. Here, we postulated that gabapentin increases expression of δ subunit-containing GABA(A) (δGABA(A)) receptors that generate a tonic inhibitory conductance in multiple brain regions including the cerebellum and hippocampus. METHODS: Cell-surface biotinylation, Western blotting, electrophysiologic recordings, behavioral assays, high-performance liquid chromatography and gas chromatography-mass spectrometry studies were performed using mouse models. FINDINGS: Gabapentin enhanced expression of δGABA(A) receptors and increased a tonic inhibitory conductance in neurons. This increased expression likely contributes to GABAergic effects as gabapentin caused ataxia and anxiolysis in wild-type mice but not δ subunit null-mutant mice. In contrast, the antinociceptive properties of gabapentin were observed in both genotypes. Levels of GABA(A) receptor agonists and neurosteroids in the brain were not altered by gabapentin. INTERPRETATION: These results provide compelling evidence to account for the GABAergic properties of gabapentin. Since reduced expression of δGABA(A) receptor occurs in several disorders, gabapentin may have much broader therapeutic applications than is currently recognized. FUND: Supported by a Foundation Grant (FDN-154312) from the Canadian Institutes of Health Research (to B.A.O.); a NSERC Discovery Grant (RGPIN-2016-05538), a Canada Research Chair in Sensory Plasticity and Reconsolidation, and funding from the University of Toronto Centre for the Study of Pain (to R.P.B.).